Effectiveness of HPV vaccine as part of national immunization program for preventing HPV infection in Thai schoolgirls after seven years post-vaccination - Pornjarim Nilyanimit; Preeyaporn Vichaiwattana; Ratchadawan Aeemchinda; Wichan Bhunyakitikorn; Thanawadee Thantithaveewat; Sunanta Seetho; Darunee Phosri; Naiyana Netthip; Nungruthai Suntronwong; Nasamon Wanlapakorn; Yong Poovorawan (Taylor & Francis Group, 2024)
Thailand introduced a two-dose regimen of bivalent HPV vaccines for Grade 5 schoolgirls, approximately 11 years old, initially piloted in Ayutthaya province in 2014, and nationwide under the National Immunization Program (NIP) in 2017. This cross-sectional, case-control study evaluated the vaccine effectiveness in schoolgirls 7 years after a two-dose administration. Between May and June 2023, 211 grade 12 female students from Ayutthaya, who received the two-dose bivalent HPV vaccine CERVARIXⓇ (HPV types 16 and 18), and 376 grade 12 students from Nakhon Pathom who did not receive the HPV vaccine, were enrolled. HPV infection was detected by testing for HPV DNA in the first-void urine samples using real-time PCR (Cobas® 4800 and AnyplexTM HPV28). The study found that the HPV vaccine 100% effective against high-risk HPV (HR-HPV) types included in the vaccine (16, 18) and 32.8% effective against other HR-HPV types not included in the vaccine. Our findings indicated that the bivalent HPV vaccine does not provide cross-protection against non-vaccine HPV types. Prioritizing vaccines with the highest coverage of HR-HPV types, such as the nonavalent HPV vaccine, is crucial to effectively prevent a broader range of HR-HPV infections under the NIP.